Intertwining properties of bounded linear operators on the Bergman space - Das, N. (Methods of Functional Analysis and Topology, 2012)
In this paper we find conditions on φ, ψL^∞(D) that are necessary and sufficient for the existence of bounded linear operators S,T from the Bergman space L_a^2(D) into itself such that for all zD, φ(z)=Sk_z, k_z, , ψ(z)=Tk_z, k_z and C_aS=TC_a for all aD where C_af=f° φ_a for all fL_a^2(D) and φ_a(z)=a-z1-a z, zD. Applications of the results are also discussed.